THE EFFECT OF THE 7E CYCLE FLIPPED CLASSROOM MODEL ON LEARNING OUTCOMES AT SMA NEGERI 5 TAKALAR (International Conference on Social and Islamic Studies, 2022)
The study aimed to determine the learning outcomes taught using the effect of the 7E cycle Flipped Classroom model on learning outcomes at SMA Negeri 5 Takalar. This study uses a quasi-experimental research design with a non-equivalent control group design. The population in this study were all students of class XI IPA SMAN 5 Takalar, 119 people. The sampling technique used purposive sampling. The sample of this research is 60 people. The data analysis technique used is descriptive analysis and inferential analysis. The inferential analysis includes normality and homogeneity tests of data and hypothesis testing using two independent sample t-tests. The categorization of learning outcomes of students who were taught using the Flipped Classroom model in the 7E cycle, namely, there were 16 students in the very high category (53%), there were 10 students in the high category (34%), and there were 4 students in the medium category (13%). While categorizing learning outcomes of students who were not taught using the Flipped Classroom model in the 7E cycle, 15 were in a low category (50%), and 15 were in the very low class (50%). Testing the hypothesis using the t-test of two independent samples shows a calculated t value of 6.764, where the value is greater than the t table value at degrees of freedom df = 58 and a significance of 0.65 is 1.701. From the statistical test results obtained by the t table value <t count, H0 is rejected, and H1 is accepted. So it can be concluded that there are differences in physics learning outcomes between students who are taught the Flipped Classroom model cycle 7E and students who are not trained using the Flipped Classroom model cycle 7E. The implication of this research is that learning the Flipped Classroom model cycle 7e can improve students' physics learning outcomes in the learning process. For this reason, it is hoped that educators will apply the Flipped Classroom model in the 7E cycle.